Joint use of polyvalent serum and immunomodulators for calves in early postnatal period - N. V. Shanshin (Ветеринария сегодня)
The paper demonstrates how a joint use of polyvalent serum and immunomodulators affects morbidity, survival, and resistance of calves in the early postnatal period.The objectives of the research are: to study how a joint administration of polyvalent serum and immunomodulators changes dynamics of morpho-biochemical and immunological blood parameters in calves; to determine an optimal ratio between the polyvalent serum and immunomodulators and frequency of administration so that to increase overall body resistance, ensure survival of calves in the early postnatal period; to assess cost-effectiveness of the joint use of polyvalent serum and immunomodulators. Research and production testing was done in Simmental calves. For this purpose one control group and five experimental groups were formed (at least 5 animals in each group). Polyvalent serum (20.0 mL) was once administered subcutaneously to the control calves on the first day of life and the animals of the experimental groups received the serum and immunomodulators according to the relevant dosing instructions. The obtained results demonstrate that the optimal protocols include a single administration of “Ribotan” in combination with serum on the first day of life, as well as a double administration of a polyvalent serum 7 days later, alternating “Fosprenil” with “Immunophane”. Administration of polyvalent serum together with an immunomodulator to newborn calves can reduce the morbidity by 70.0% and achieve 100.0% survival, improving this indicator by 22.3% compared to the control. Cost-effectiveness assessment of the veterinary measures specified in these protocols shows that each rouble spent on the measures saves 25.29 roubles. To increase nonspecific resistance of calves in the early postnatal period, preference shall be given to those veterinary medicinal product that can not only normalize the immune system, but also have a combined positive effect on homeostasis in general, stimulate the growth and development of young animals at the early stages of ontogenesis.